Wavelet‐based numerical techniques for 1D peristatic problems in infinite domain. (3rd February 2020) - Singh, Debabrata; Panja, Madan Mohan
Abstract : Peristatics is an important branch of continuum mechanics dealing with nonlocal effects in solid structures. Some 1D peristatic problems with four different micromodulus functions have been studied here. A wavelet‐based collocation method has been developed to find multiscale approximate solutions of the peristatic problems that avoid cumbersome evaluation of singular type integrals present in analytical solution available in literature. The obtained results offer important insights into applications and simulations of peristatic models and seem to be useful for investigation in the field of peridynamics in one or higher dimensions.